2017
DOI: 10.1002/rra.3217
|View full text |Cite
|
Sign up to set email alerts
|

The use of behavioural metrics to evaluate fishway efficiency

Abstract: Fishways are installed worldwide to facilitate accessibility to functional habitats and to increase the ecological continuity of rivers. Their evaluations are increasing, but complete studies in the field with wild individuals are still scarce. In the lower Bocq River (Belgium), a pool type fishway was installed in 2011. A combined passive-integrated-transponder-tag and radio-telemetry system was designed and installed downstream of the dam and in the fishway to analyse fine-scale individual fish behaviour. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…Other authors used the technique of capturing fish at the top of fishways and subsequently evaluating reascension (Pont et al 2009;Thiem et al 2013;Harty et al 2016). Our intra-and inter-river translocation method did not affect their spawning migration behaviour, as was already observed with the rheophilic cyprinid nase (Ovidio et al 2016), the trout, and the grayling (Ovidio et al 2017). It also has the advantage of avoiding habituation behaviour due to the recurrence of the passage and the associated possibility of learning, which may influence the ability of individuals to find the entrance of the fishway more rapidly.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Other authors used the technique of capturing fish at the top of fishways and subsequently evaluating reascension (Pont et al 2009;Thiem et al 2013;Harty et al 2016). Our intra-and inter-river translocation method did not affect their spawning migration behaviour, as was already observed with the rheophilic cyprinid nase (Ovidio et al 2016), the trout, and the grayling (Ovidio et al 2017). It also has the advantage of avoiding habituation behaviour due to the recurrence of the passage and the associated possibility of learning, which may influence the ability of individuals to find the entrance of the fishway more rapidly.…”
Section: Discussionsupporting
confidence: 57%
“…Finally, a total of five fish (n = 4 barbel, n = 1 chub) were single-tagged with an RFID transponder (Table 2). The fish were surgically tagged following the procedure described by Ovidio et al (2017) and Benitez et al (2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Raabe et al (2019) adjusted their passage efficiency metric to reflect that imperfect detection efficiency probably led to underestimated passage efficiency. Ovidio et al (2017) reported “overall passage efficiency” as the number of successfully passed fish divided by the total number released, and the “adjusted passage efficiency” as the number of successfully passed fish divided by the number that was attracted, which is actually how passage efficiency is defined for this meta‐analysis. Only unadjusted metrics and data were used for this analysis.…”
Section: Methodsmentioning
confidence: 99%